Self-Regulation, Conformity, and the Procrastination Puzzle: A Mediated Path Analysis Among University Students - Mafazah Daulay, Sarah; Hasanuddin, Hasanuddin; Sari Dewi, Salamiah (JESS (Journal of Education on Social Science), 2025)
Academic procrastination undermines student achievement worldwide; yet, prior evidence on its antecedents focuses almost exclusively on individual-level self-regulation, while overlooking social pressures. This study investigates whether peer conformity mediates the relationship between self-regulation and procrastination among university students, thereby integrating cognitive-behavioural and sociocultural perspectives. A cross-sectional survey was administered to 428 undergraduates (Mage = 20.1 ± 1.4 years; 63 % female) recruited via stratified random sampling across four Indonesian universities. Participants completed validated Indonesian versions of the Short Self-Regulation Questionnaire, the Academic Procrastination Scale, and the Peer Conformity Scale. After confirmatory factor and reliability analyses, a latent-variable path model with a 5,000-sample bootstrap was tested in AMOS to estimate direct and indirect effects. The measurement model demonstrated good fit ( χ ² /df = 1.89, CFI = 0.962, TLI = 0.955, RMSEA = 0.046). Self-regulation negatively predicted conformity ( β = − 0.46, p < .001) and procrastination ( β = − 0.31, p < .001). Conformity positively predicted procrastination ( β = 0.35, p < .001). A significant indirect path confirmed that conformity partially mediates the self-regulation – procrastination link ( β indirect = − 0.16, 95 % CI [ − 0.23, − 0.10]), accounting for 34 % of the total effect. Findings extend social-cognitive models of delay behaviour by showing that low personal control heightens susceptibility to peer-norm pressures, intensifying procrastination. Interventions should pair self-regulatory training with strategies that recalibrate classroom norms (e.g., collaborative goal setting) to curb academic delay .